Akuntabilitas Dalam Penyelenggaraan Surat Pertanggungjawaban Perjalanan Dinas Gubernur Di Kantor Gubernur Provinsi Jawa Timur - Ananda, Aliefa Rizkya; Nafi'ah, Binti Azizatun (JURNAL ILMIAH ILMU ADMINISTRASI, 2023)
This research aims to explain how accountability is implemented in organizing the Governor's Official Travel SPJ at the Governor's Office of East Java Province. Qualitative methods with purposive sampling techniques were used to explore more deeply those who have knowledge of the research topic. By referring to the 7 indicators of accountability from Mardiasmo (2018), namely planning, control, fiscal policy, politics, coordination and communication, performance assessment, and motivation. The results of this research indicate that the implementation of the Governor's Official Travel SPJ at the Governor's Office of East Java Province has carried out accountability quite well. SPJ accountability for regional finances requires regulations and monitoring of employee performance. However, control and planning without motivation, communication and coordination between employees will cause inconsistency in each other's performance.